TLR4-induced NF-κB and MAPK signaling regulate the IL-6 mRNA stabilizing protein Arid5a - Nyati, Kishan K. (Nucleic Acids Res, 2017)
The AT-rich interactive domain-containing protein 5a (Arid5a) plays a critical role in autoimmunity by regulating the half-life of Interleukin-6 (IL-6) mRNA. However, the signaling pathways underlying Arid5a-mediated regulation of IL-6 mRNA stability are largely uncharacterized. Here, we found that during the early phase of lipopolysaccharide (LPS) stimulation, NF-κB and an NF-κB-triggered IL-6-positive feedback loop activate Arid5a gene expression, increasing IL-6 expression via stabilization of the IL-6 mRNA. Subsequently, mitogen-activated protein kinase (MAPK) phosphatase-1 (MKP-1) promotes translocation of AU-rich element RNA-binding protein 1 (AUF-1) from the nucleus to the cytoplasm, where it destabilizes Arid5a mRNA by binding to AU-rich elements in the 3΄ UTR. This results in downregulation of IL-6 mRNA expression. During the late phase of LPS stimulation, p38 MAPK phosphorylates Arid5a and recruits the WW domain containing E3 ubiquitin protein ligase 1 (WWP1) to its complex, which in turn ubiquitinates Arid5a in a K48-linked manner, leading to its degradation. Inhibition of Arid5a phosphorylation and degradation increases production of IL-6 mRNA. Thus, our data demonstrate that LPS-induced NF-κB and MAPK signaling are required to control the regulation of the IL-6 mRNA stabilizing molecule Arid5a. This study therefore substantially increases our understanding of the mechanisms by which IL-6 is regulated.